The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/0104-6632.20150321s00003124
|View full text |Cite
|
Sign up to set email alerts
|

RECOVERY OF CYCLODEXTRIN GLUCANOTRANSFERASE (CGTase) USING IMMOBILIZED METAL CHELATING AFFINITY CHROMATOGRAPHY

Abstract: -Immobilized metal affinity chromatography (IMAC) was chosen as a method of purification for the recovery of CGTase from E. coli homogenate. E. coli harbouring the Bacillus sp. G1 gene expressed extracellularly secreted CGTase into ampicillin supplied LB broth. Culture was pre-purified using SnakeSkin dialysis tubing (3.5 MWCO) with an enzyme activity of 147.80 U/mL. Three strategies (A, B and C) were employed for the purification of CGTase using column adsorption chromatography with Ni 2+ -Sepharose resin. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…The findings demonstrated that although Mg 2+ , Co 2+ , and Cu 2+ inhibited the secretion of CGTase, Fe 3+ may increase the activity of CGTase (11.5 U/mL) and biomass of the strain. The CGTase secretion was unaffected by the metal ions Mn 2+ and Ca 2+ ( Li et al, 2010 ; Sivapragasam and Abdullah 2015 ; Li et al, 2018 ). It is stopped growing the fermentation & the strain's growth on reaching 40th h of fermentation, the supernatant's CGTase production reached at optimum limit at 46.54U/mL ( Wang et al, 2018 ; Zhou et al, 2023 ).…”
Section: Protein Engineeringmentioning
confidence: 99%
“…The findings demonstrated that although Mg 2+ , Co 2+ , and Cu 2+ inhibited the secretion of CGTase, Fe 3+ may increase the activity of CGTase (11.5 U/mL) and biomass of the strain. The CGTase secretion was unaffected by the metal ions Mn 2+ and Ca 2+ ( Li et al, 2010 ; Sivapragasam and Abdullah 2015 ; Li et al, 2018 ). It is stopped growing the fermentation & the strain's growth on reaching 40th h of fermentation, the supernatant's CGTase production reached at optimum limit at 46.54U/mL ( Wang et al, 2018 ; Zhou et al, 2023 ).…”
Section: Protein Engineeringmentioning
confidence: 99%